Overcoming the damage of rice to iron toxicity:Screening on Hydroponic Solution and Soil Pot Experiment - Unoki, Saeka; Sitaresmi, Trias; Ehara, Hiroshi; Nugraha, Yudhistira (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
Iron toxicity affects the growth and yield of rice plant. Overcoming the damage of rice production by iron toxicity requires furthermore researches from laboratory to field levels. Here, we study responses of rice genotypes to iron toxicity between vegetative stage in hydroponic and whole grow stages in the pot. The first experiment was hydroponic experiment using twelve rice genotypes which were growth in the Yoshida Solution with addition of 0.2 % of agar. Three level of iron was given at 0, 500 and 700 ppm. The second experiment was the pot experiment using alluvial soil added with 3.000 ppm of ferrous combine with four levels of potassium and the control on Cilamaya Muncul (tolerant), Inpara 8 (moderate tolerant) and IR 64 (susceptible). In hydroponic experiment, even though the symptom appeared obviously, the leaf bronzing score (LBS) of tolerant and sensitive genotypes were not different. Physiological traits were significantly affected by Fe treatment in all varieties. Then symptom and physiological traits were significantly correlated. Through the pot experiment, it was confirmed the tolerance of each varieties. However, we couldn’t see the correlation between the LBS on hydroponic and soil at this time. And the heading delay was new finding, but it depended on varieties. We also could see the possibility of potassium application to inhibit iron toxicity but still we need to explore how it works. Kata kunci: iron toxicity, rice, hydroponic, soil